The Role of 'Assitalliang'-Based Learning Materials in Enhancing Cultural Awareness in Indonesian Language Learning at Higher Education Institutions - Wahyuddin, Wahyuddin; Ramli, Ramli; Anshari, Anshari (Journal of Ecohumanism, 2025)
Indonesia, as a country with rich cultural diversity, faces challenges in maintaining and developing cultural awareness among the younger generation, especially in higher education environments. Effective learning of the Indonesian language not only teaches linguistic aspects but also needs to instill the cultural values embedded in the language. 'Assitalliang', as one of the local cultural concepts rich in wisdom values, has the potential to become an effective teaching material for this purpose. 'Assitalliang', as one of the local cultural concepts rich in values of wisdom, has the potential to be an effective teaching material for this purpose. This research aims to examine the role of 'Assitalliang'-based teaching materials in enhancing students' cultural awareness in Indonesian language learning at higher education institutions. A qualitative approach with a case study design was used at one tertiary institution in Indonesia, with data obtained through in-depth interviews with lecturers and students, observation of the learning process, as well as analysis of teaching materials and student assignments. Data analysis was conducted thematically to identify the contributions of 'Assitalliang' teaching materials to the development of cultural awareness The research findings indicate that teaching materials based on 'Assitalliang' not only enrich the linguistic aspects of learning but also provide a contextual experience that allows students to understand and embody local cultural values such as gotong royong (mutual assistance), respect, togetherness, and social harmony. These findings emphasize the importance of developing teaching materials that integrate cultural aspects as a holistic approach in learning the Indonesian language. Thus, the 'Assitalliang' based teaching materials can serve as an effective model for internalizing cultural values while also strengthening students' national identity.